FORMAL SEARCH AND REFERRALS FROM A FIRM'S PERSPECTIVE - Martina Rebien; Michael Stops; Anna Zaharieva (International Economic Review, 2020)
We explore the relationship between firms' characteristics and recruitment strategies. We present a theoretical search model with two search channels: a costly formal channel and a costless informal channel (referrals). We empirically test the model predictions and find that: larger firms search more formally; firms search more formally for high-skilled workers; the positive relationship between firm's size and formal search intensity also holds for firms not using referrals; firms using referrals invest less into formal search compared to firms not using referrals; larger firms hire less often by referrals than smaller firms; and larger search effort leads to more~applicants.
Keywords: 330